Pengaruh Penggunaan Media Sosial terhadap Prestasi Belajar Siswa Sekolah Menengah Atas - Didit Darmawan; Tasya Aulia Rizka; Rahayu Mardikanigsih (Simpati, 2026)
High school students are increasingly familiar with the digital world, particularly through various social media platforms they use in their daily lives. These activities are shaping new patterns of interaction in how they seek information, communicate, and complete school assignments. Social media also makes it easier to access learning resources and expand students' knowledge. However, on the other hand, excessive use can reduce their focus on studying by causing distractions. Therefore, social media significantly influences students’ behavior and academic achievement as an external factor in the learning process. While some students use it for academic purposes, others experience a decline in motivation and focus due to excessive use. This study is a literature review using a Systematic Literature Review (SLR) approach, aimed at synthesizing various research findings regarding the effect of social media use on high school students’ academic achievement. Data were obtained from articles, theses, and conference proceedings via Google Scholar, using inclusion criteria that encompassed quantitative studies discussing the intensity, purpose, and patterns of social media use among high school students. The findings indicate that social media use has a significant effect on academic achievement, both positive when used for academic purposes and negative when used excessively and without control.